Fasilitas IKM dalam Bentuk Produksi - Herli Antoni; Muhammad Daniel Nurrohmat; Muhamad Firli Haikal; Rusli Fadli; Tubagus Aswin (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
The research aims to explore and analyze facilities in the form of production available to small and medium-sized industries (SMEs) using a qualitative approach through library studies. ICTs play an important role in the economy, especially in developing countries, but they often face challenges in increasing their production and competitiveness due to the limitations of available facilities. This research uses qualitative methods with a focus on the analysis of library studies relevant to the problems of production facilities in IKM. Data is collected through scientific literature, books, journal articles, research reports, and other sources of information related to this topic. The analysis is carried out to identify and analyze key aspects related to production facilities in ICT, such as the types of facilities available, the challenges faced, and the strategies used to overcome such limitations. The results of this study revealed that production facilities in the form of equipment, machines, and physical infrastructure are generally limited to ICTs. These limitations affect the productivity and efficiency of ICTs as well as their ability to meet increasingly complex market requirements. In addition, external factors such as government regulations, access to resources, and the availability of financial support also affect the quality and accessibility of production facilities within ICT. This research provides an in-depth insight into the challenges and complexities associated with production facilities within IKM. In a qualitative context, the research also reveals strategies and initiatives taken by ICT to address facility constraints, such as collaboration with third parties, cross-sector collaboration, and the use of information and communication technologies. These findings provide a better understanding of the ways that ICTs can take to improve their production and competitiveness in limited contexts. This research shows the importance of further research in terms of production facilities in ICT with a qualitative approach and through library studies. It is expected that these findings will provide a strong foundation for the development of policies, best practices, and strategies that can help strengthen production facilities in ICTs and drive sustainable economic growth.